Laser acupuncture reduces pain in pediatric kidney biopsies: a randomized controlled trial. Issue 1 (January 2017) - Oates, Aris; Benedict, Kelly A.; Sun, Karen; Brakeman, Paul R.; Lim, Jessica; Kim, Cynthia
Abstract : Abstract: Evaluate laser acupuncture (LA) as an adjuvant therapy in pain management during percutaneous kidney biopsy procedure in children and adolescents. This prospective, double-blinded, randomized controlled trial enrolled patients aged 7 to 26 years admitted to a children's hospital for percutaneous kidney biopsy. Patients received LA to treatment points (acupuncture group) or sham points (control group) before the procedure. The laser delivered a dose of 42 J/cm 2 over 10 acupoints. Patients and parents rated the pain during and after the biopsy, and change in pain scores were calculated for each patient. Anxiety, vital signs, sedation medication, and patient's biopsy experience were secondary outcomes. Sixty-nine treatments (33 in the acupuncture group and 36 in the control group) were eligible for analysis. Patients in the acupuncture group reported a significantly improved change in the pain score after the biopsy compared with the controls (0.8 vs −0.5, P = 0.044). Patients in the acupuncture group had a statistically significant decrease in procedure vital signs including heart rate (−1.8 vs 5.6, P = 0.043) and respiratory rate (−2.4 vs 0.4, P = 0.045) when compared with controls. Parents also perceived a correspondingly greater improvement in their child's pain for those in the acupuncture group compared with the controls (2.3 vs 0.3, P = 0.04). Adjunctive LA significantly improved pain after pediatric percutaneous kidney biopsies. Abstract : This first, randomized controlled trial of laser acupuncture in procedural pain management for kidney biopsies suggests that it can reduce pain and improve the procedure experience.